The Analysis of Qualitative Properties of Mine's LaborForces Effects on Productivity and Wages - Reza Shakor shahabi; Reza Kakaei; Reza Ramazani (آموزش مهندسی ایران, 2009)
Mines as an important sector of economy has a basic role in the supply chain of most economical sectors. The analysis of quality and quantity of labor force in mines is one of the necessary activities for efficient management. This paper describes the relationship between qualitative properties with labor wage and productivity indexes of Iran mines labor force. For this purpose, qualitative and quantitative properties of labor forces have been evaluated in the period of 1994-2003 based on the experience, education, research and development, training and skills. The quantitative properties of labor force include labor wage and labor productivity. In the next step, relationships between qualitative and quantitative have been evaluated with Eviews software based on information of 8 provinces of Iran. Results show the effects of knowledge level and labor force wage on the labor force productivity. In addition, the skill level has no effect on the mine labor force wages.